MEDIA QUIZIZZ SEBAGAI APLIKASI EVALUASI PEMBELAJARAN KELAS VI DI SDN GUNTUR KOTA CIREBON - Herlina Pusparani (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This study aims to describe quizizz application as a learning evaluation application for 6th grade SDN Guntur Cirebon City and improve learning evaluation results through quizizz as a fun learning application. This classroom action research was conducted in two cycles with two learning meetings in each cycle. Each cycle consists of planning, implementing, observing, and reflecting. Every meeting, students work on learning evaluations through quizziz. The subjects of this study were 32 students of class VI A SDN Guntur, Cirebon City. The results of this study indicate that quizizz is one of the learning media for learning evaluation activities. Quizizz is an online application that can be accessed via a computer, laptop or smartphone. The advantage of this application is that it can use images, sounds, and animations. There is an interaction when students work on learning evaluations, so that students feel motivated to do the evaluation and feel happy. Students can improve their learning outcomes as indicated by the increase in quizizz results. In the first cycle of the first meeting, the number of students who completed was 37.5%. This result increased in the first cycle of the second meeting to 62.5%. In the second cycle of the first meeting, completeness reached 87.5%, and in the second cycle of the second meeting, completeness reached 100%. All students can achieve completeness in the evaluation of learning because students are increasingly motivated to be able to do quizzes, so that students' understanding of the material increases. This causes the learning outcomes of students to increase. Keywords: learning evaluation, media, quizizz